PERANCANGAN ULANG TATA LETAK DAN FASILITAS DI PT. XY DENGAN ALGORITMA COMPUTERIZED RELATIVE ALLOCATION OF FACILITIES TECHNIQUE (CRAFT) - Arya Gilang Rosmarwanto (2022)
PT. XY is a meatballs-based company with various types of meatballs. This company uses a make to order (MTO) system to fulfill orders and used jobshop as their production flow. In terms of layout, PT. XY has a number of problems related to distance, namely the location of the raw material warehouse which is far from each other from the production room. Therefore, to solve this problem, the CRAFT algorithm is used as a solution for optimizing the layout at PT. XY. In this research, the CRAFT algorithm was run by two different software: WinQSB 2.0 and Microsoft Excel with Facility Layout Add-Ins. As a result, WinQSB 2.0 propose a layout with the result of material handling's moment is equal to 6,534.79 m/day or shortening the overall distance by 5% and the mass of material handling by 29,397 kg or lightening the load by 13% of the actual layout. Meanwhile, the results of improvements through Microsoft Excel Facility Layout Add-Ins gave the moment and mass of material handling by 6,773.57 m/day and 31,417 kg, which each of them was 1% and 7% more efficient than the actual layout. Then, each of actual layout's results has a moment and mass of material handling by 6,856.48 m/day and 33,881 kg. From these results, the solution given by WinQSB 2.0 became the best layout suggestion for PT. XY.